(3HSJGf GdYGQajf GdCRgGQ aj efGbH ReRe GdCNHGQ heYGOf GdCfhGQ SjOj CMeO Hf jhSa GdQGTOj GdfSH (B[(3hGdOGQ(B]s - (3CHh YHO Gddg eMeO Hf eMeO Hf CMeO GdUHGZ GdbdYjs ((3YHOg eMeO Hf YeQ s)
(3ChdgG (B:s
(3hHYO aEfi QCjJ Ggd bdYJfG hSGFQ eYGTQ ghGQI hHfi QGTO hZjQge jMSf ai GdTjN CMeO Hf jhSa Hf QGTO s
(3BNQgG (B:s
(3hJdGePI GdTjN SjOi CMeO Hf jhSa dGjMUi YOge EdG Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B254 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B362 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B64 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(243 (3c(B) s
Keywords: (3GdJGQjNs